New records of freshwater Dinoflagellates from Bangladesh. I. Ceratium, Gymnodinium and Peridinium - Khondker, Moniruzzaman; Aziz, Abdul; Alfasane, Md Almujaddade; Bhuiyan, Rauf Ahmed (Bangladesh Journal of Botany, 2010)
Ten species of dinoflagellates from freshwater domestic ponds of Pirojpur and Barisal districts, Bangladesh, have been reported for the first time. The taxa are Ceratium hirundinella var. furcoides, Gymnodinium aeruginosum, G. coronatum, G. veris, Peridinium aciculiferum, P. allorgei, P. cinctum fa. westii, P. cunningtonii tab. remotum var. wildemani, P. gatunense and P. goslaviense. Key words: Freshwater algae; Dinoflagellates; Ceratium; Gymnodinium; Peridinium; Bangladesh DOI: 10.3329/bjb.v38i1.5119 Bangladesh J. Bot. 38(1): 65-69, 2009 (June)